Enhancing Political Participation through Civic Education: Integrating Digital and Social Media for Peaceful Elections among Generation Z in Indonesia - Wijaya, Mirza Mahbub; Amalia, Hamsar Suci (MyResearch ID Publishing, 2024)
Purpose – This study investigates the role of civic education in shaping political participation among Generation Z in Indonesia, particularly in the context of peaceful elections. It aims to address the gap in understanding how the integration of digital and social media within civic education can empower young voters to engage constructively in the democratic process. Methods/Design/Approach – The study employs a conceptual approach using Theory Synthesis to integrate fragmented theories and literature on civic education, youth political participation, and peaceful elections. The literature was selected based on specific criteria, ensuring relevance to the subject matter. Data were synthesized to create a cohesive theoretical framework that connects the role of civic education with the political engagement of Generation Z. Findings – The study found that effective civic education, which integrates digital technology and social media, can significantly enhance Generation Z's political awareness and active participation. The findings suggest that current civic education curricula need to be updated to reflect the digital realities of Generation Z, thus improving the quality of their participation in elections and supporting a more peaceful democratic process. Originality/Value – This research contributes to the field by proposing a more adaptive civic education model that aligns with the technological inclinations of Generation Z. It offers a novel perspective by highlighting the importance of social media as a tool for political learning and engagement, an area often overlooked in existing studies. Practical Implications – The study underscores the need for educational policymakers to revise civic education curricula, incorporating digital and social media tools to better engage Generation Z. Implementing these changes could enhance the political literacy and participation of young voters, ultimately supporting more democratic and peaceful elections in Indonesia. Keywords Civic education, generation Z, political participation, peaceful elections, digital integration Paper type Conceptual paper